DIAGNOSTIC OF EFFICIENCY OF FOREIGN ECONOMIC - KARACHYNA, NATALIA; SMETANIUK, OLENA; VITIUK, ANNA; MUKOID, DARIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is dedicated to solving the scientific task of generalizing theoretical and methodological approaches to detecting the efficiency of foreign economic activity in modern economic conditions, depending on goals and expectations of the stakeholders. The analysis of works of domestic research scientists on the concept essence of efficiency of foreign economic activity has shown the need to study it as an integrated category that characterizes the enterprise’s potential and level of achieving foreign economic activity goals. It has been proven in the article that amidst business internationalization, the successful development of foreign economic activity of an enterprise is determined by its ability to solve the issues of accurately assessing the results of such an activity and increasing its efficiency. Thus, the efficiency of foreign economic activity of an enterprise needs to be detected based on the actual efficiency of separate operations (separate directions) of foreign economic activity and in comparison with the set goals that have to do with each separate operation (separate direction). Considering the fact that the efficiency of foreign economic activity is a relative concept, the factors that influence the formation of income and expenditure have been studied, as well as the need for an enterprise to respond flexibly to the change of these factors, as it has direct influence on the results of its economic activity. The critical analysis of approaches to assessing the efficiency of foreign economic activity has revealed that there usually tend to be two directions: the efficiency of export-import operations and the overall efficiency of foreign economic activity, that directly depend on the absolute profit value, however, this does not take into account the fact that foreign economic activity is tightly connected with other areas of an enterprise, which do not have a clear financial expression, and, thus, are ignored in such approaches. The expediency of using methods of complex diagnostic of foreign economic activity, which provides a choice of an optimal way of entering the foreign market and prolonging its effective functioning there, has been substantiated. It is noted that the diagnostic of the efficiency of foreign economic activity is a process of identification and analytical assessment of the influence that different factors have on foreign economic activity of an enterprise in order to reveal and solve all the existing and probable problems in the field of maintenance and performance of particular actions (stages) of entering foreign (international) markets and ensuring sustainable functioning there. Based on the conducted analysis, diagnostic of the efficiency of foreign economic activity is suggested to be carried out in 3 stages (informational and analytical support stage, analytical and calculation stage and management stage) and the content of each stage is revealed.